Macro- and micronutrient intakes among severely malnourished under-five children during the economic crisis in Yogyakarta - Endy P Prawirohartono; Atiek Werdiningsih (Indonesian Pediatric Society Publishing House, 2016)
Objective To evaluate macro and micronutrient intakes among under five-year children with severe malnutrition during the period of economic crisis. Methods We conducted a longitudinal study from August until November 2000 in Bantul and Sleman districts, Yogyakarta Spe- cial Territory of Indonesia. Two-weekly home visits were performed to collect data about food intakes. Results Of 46 children, 26 experienced an improvement in nutri- tional status, whereas 20 children did not. The median intakes of macro and 8micronutrients were lower than the Recommended Daily Allowances (RDA), ranged from 22% (vitamin C) to 69% (phosphorus), except for vitamin A (406%). The median intakes of protein, vitamin A, thiamin, vitamin C, calcium, iron and phospho- rus were higher in severely malnourished children who experienced improvement in nutritional status compared to children who did not, and in breastfed compared to non-breastfed, but Mann Whitney U-test was not able to detect significant differences (p>0.05). Strati- fication using age group showed that calories and thiamin intakes of older children (348 months) were lower than those of younger children (Kruskal Wallis tests p = 0.016 and 0.022 respectively). Conclusions The macro and micronutrients intakes of severely malnourished under five-year children were lower than RDA, ex- cept for vitamin A. There were differences in nutrient intakes ac- cording to the improvement in nutritional status and age group